Conceptual Change Text based Analogy Model to Remedy Misconceptions on Eye Optics - Palerangi, Andi Muadz; Wahyuni, A. Sri Astika; Nurlaela, Nurlaela (Publikasi Pendidikan, 2024)
Misconception is well-known as barrier to students in learning science, and many studies have tried to investigate the type of misconception and try to remediate the common misconception after finding the cause of it. A study about how to provide information about an overview of the eye optics concept in physics was conducted to analysis pre-service teacher misconceptions about the eye optics and provide solutions with conceptual change text-based analogy model in learning processing qualitatively. Data were collected from Open ended question in worksheet of exploration phase (WEF) and Open-ended question in worksheet of concept application phase (WCA). The study resulted in explanation that misconceptions occur in the preservice teacher, especially in the matter of the eye optics. There are three types of Misconceptions. Firstly, They thought that: 1) many understand that the eye as is a biological study and which is the five senses in living things/human body and the rather than they do not understand the eyes as an optical instrument that can detect light and how the eye itself can see objects as a result of the light reflecting process that occurs in the eye ; 2) in determining the nature of the image formed in the eye, it was written based on the experience of seeing in everyday life, namely: real, upright, equal in size. In fact, if it is depicted using a graph using the principle of the passage of light, then the nature of the image formed on the eye is real, inverted, and reduced. ; and 3) in determining the type of lens needed for those whose eyes have problem to be able to see properly that can be used by people with eye defects does not first determine the strength of the lens but is determined based on the type of eye defect suffered. For example, near sighted people (hypermetropy) use glasses with concave lenses and people with farsightedness (myopia) use convex lenses. So that when they encounter problems in the application of concepts to determine the strength of the lens for sufferers of eye defects, both near sighted and farsighted, they tend to be wrong because they do not pay attention to the use of a negative sign (-) in the object's image distance which is calculated mathematically. They immediately determine the power of the lens by solving it mathematically and later at the end of the new solution then they are given a mark based on the type of lens used for people with eye defects.